Designing explanations in the recommender systems based on the principle of a black box - Chalyi, Serhii; Leshchynskyi, Volodymyr; Leshchynska, Irina (Національний технічний університет "Харківський політехнічний інститут", 2019)
The subject matter of the article is the process of designing of explanations in the recommender system. The goalis to develop a conceptual model for designing explanations in recommender systems based on the black box principle. Such a model binds the conditions, the result and the constraints on the choice of objects from the user's position.The user should receive justification of the recommendations taking into account context-oriented possibilities of using the proposed objects.Tasks: to adapt the principle of a black box to the task of constructing explanations in the recommender system; to develop a conceptual scheme for constructing explanations according to the functional principle; to develop a conceptual model for the designing of explanations based on the principle of a black box.The principle used is: functional, or the principle of a black box.The following resultsare obtained. The principle of the black box to the problem of constructing explanations in the recommender system was adapted. The conceptual scheme of constructing explanations on the basis of a functional principle is developed, taking into account both the properties of objects and the sequences of their use. The conceptual model of the explanation based on the black boxprinciple is developed.Conclusions.Scientific novelty of the results is as follows.The conceptual model for constructing explanations with recommendations on the functional principle or the principle of a black box is proposed. The model takes into account the characteristics of subjects and consumers, information on the use of objects in the subjectarea, as well as recommendations in the form of a list of objects.The advantage of using the proposed model lies in the fact that it takes into account the methods of applying the recommended objects for constructing explanations. This creates conditions for personalizing recommendations in cases of a cold start of the recommender system, as well as artificial increase in the ratings of individual items.

Предметом вивчення в статті є процеси формування пояснень в рекомендаційних системах. Метою є розробка концептуальної моделі формування пояснень в рекомендаційних системах за принципом чорного ящику. Така модель зв’язує умови, результат та обмеження щодо вибору об’єктів з позицій користувача. Користувач має отримати обґрунтування рекомендацій з урахуванням контекстно-орієнтованих можливостей використання запропонованих об’єктів. Завдання: адаптувати принцип чорного ящику до задачі побудови пояснень в рекомендаційній системі; розробити концептуальну схему побудови пояснень за функціональним принципом; розробити концептуальну модель формування пояснень за принципом чорного ящика. Використовуваними принципами є: функціональний, або принцип чорного ящику. Отримані наступні результати. Адаптовано принцип чорного ящику до задачі побудови пояснень в рекомендаційній системі. Розроблено концептуальну схему побудови пояснень на основі функціонального принципу з врахуванням як властивостей об’єктів, так і послідовностей їх використання. Розроблено концептуальну модель формування пояснень за принципом чорного ящику. Висновки. Наукова новизна отриманих результатів полягає в наступному. Запропоновано концептуальну модель побудови пояснень до рекомендацій за функціональним принципом або принципом чорного ящику. Модель враховує характеристики предметів та споживачів, інформацію про використання об’єктів в предметній області, а також рекомендацію у вигляді переліку об’єктів. Переваги застосування запропонованої моделі полягають в тому, що вона враховує способи застосування рекомендованих об’єктів для побудови пояснень. Це створює умови для персоналізації рекомендацій у випадках холодного старту рекомендаційної системи, а також штучного збільшення рейтингів окремих предметів.
Побудова пояснень в рекомендаційних системах за принципом чорного ящику
Keywords: e-commerce systems; the formation of recommendations; the formation of explanations; системи електронної комерції; контекст прийняття рішень; формування рекомендацій; формування пояснень